Development Of Social Media-Based One-Stop Microlearning Videos - Ebzy, Fadiza Nova; Adi, Eka Pramono; Utami, Deka Dyah (Universitas Negeri Malang, 2024)
This research is motivated by the fact that the learning process at Taman Siswa Junior High School has not yet utilized technology-based media in teaching. The findings from observations reveal that the learning media currently used do not meet the needs of Generation Z. The purpose of this research is to produce instructional video media to facilitate the learning process of seventh-grade students at Taman Siswa Junior High School on Procedure Texts. This type of research is development research or research and development (R&D) using the Sadiman development model. The researcher chose the Sadiman model because it is designed to develop learning media in the form of audio, video, and film. The steps taken include (1) Needs analysis, (2) Formulating objectives, (3) Formulating materials, (4) Developing measurement tools, (5) Scriptwriting, (6) Media production, (7) Validation, (8) Revision, and (9) Final product. The sample consists of 30 seventh-grade students at Taman Siswa Junior High School. The research